Multi-scenario simulations of future land use and ecosystem services in wetland ecosystems of Binhai, Tianjin - Yue, Ang; Guo, Xueer; Gong, Haiying; Ma, Li; Wang, Wanfeng (Frontiers in Environmental Science, 2025)
This study used remote sensing images from 2000 to 2020 to explore changes in the ecological value of the four wetland nature reserves in Binhai, Tianjin. By integrating the PLUS model and ecosystem service value (ESV) assessment methods, this study explored the spatiotemporal evolution of the Binhai wetland ecosystem from 2000 to 2020 and systematically simulated land use changes and their impacts on ESVs under three scenarios: natural development, economic development, and ecological conservation. The results showed that (1) from 2000 to 2020, the overall ecological value of the four reserves showed a growth trend, with the added value of aquatic ecosystems making the most significant contribution. Among ecosystem services, hydrological regulation played a crucial role in supporting the total ESV and significantly surpassed the other service categories. (2) The spatial aggregation and total ESV exhibited distinct variations under different development scenarios. Changes in cultivated land, water bodies, and impervious surfaces were particularly significant. While human interventions under different development objectives strongly influenced land use structures, the dominant roles of cultivated land and water bodies remained largely unchanged. (3) The various ESV components and individual ESV values in the four reserves showed notable differences under the different development scenarios. Under the ecological conservation scenario, both the overall and individual ESVs increased, whereas under the economic development scenario, they declined.